MicroRNAs-Based Inter-Domain Communication between the Host and Members of the Gut Microbiome - Williams, Maggie R.; Stedtfeld, Robert D.; Tiedje, James M.; Hashsham, Syed A. (Frontiers in Microbiology, 2017)
The gut microbiome is an important modulator of host gene expression, impacting important functions such as the innate immune response. Recent evidence suggests that the inter-domain communication between the gut microbiome and host may in part occur via microRNAs (small, non-coding RNA molecules) which are often differentially expressed in the presence of bacteria and can even be released and taken up by bacteria. The role of microRNAs in microbiome – host communication in intestinal diseases is not fully understood, particularly in diseases impacted by exposure to environmental toxicants. Here we review the present knowledge in the areas of microbiome and microRNA expression- based communication, microbiome and intestinal disease relationships, and microRNA expression responses to intestinal diseases. We also examine potential links between host microRNA– microbiota communication and exposure to environmental toxicants by reviewing connections between i) toxicants and microRNA expression, ii) toxicants and gut diseases, and iii) toxicants and the gut microbiome. Future multidisciplinary research in this area is needed to uncover these interactions with the potential to impact how gut-microbiome associated diseases (e.g., inflammatory bowel disease and many others) are managed.